2018
DOI: 10.3390/ijms20010098
|View full text |Cite
|
Sign up to set email alerts
|

IL-8 Secreted from M2 Macrophages Promoted Prostate Tumorigenesis via STAT3/MALAT1 Pathway

Abstract: Prostate cancer (PCa) is a major health problem in males. Metastasis-associated with lung adenocarcinoma transcript-1 (MALAT1), which is overexpressed in PCa tissue, is associated with physiological and pathological conditions of PCa. M2 macrophages are major immune cells abundant in the tumor microenvironment. However, it remains unknown whether M2 macrophages are involved in the effects or not, and molecular mechanisms of MALAT1 on PCa progression have not yet been comprehensively explored. Here we reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…Kan et al reported that CCL5 derived from tumor-associated DCs was associated with the up-regulation of MALAT1, which subsequently increased the expression of Snail to promote tumor progression (42). A recent study also reported that IL-8 secreted from M2 macrophages sufficiently promoted the expression level of MALAT1 by activating the STAT3 signaling pathway (78). These studies suggest that MALAT1 serves as a key regulator during tumor progression, especially during tumor immune evasion.…”
Section: Expression Of Molecules In Tumor Cellsmentioning
confidence: 96%
“…Kan et al reported that CCL5 derived from tumor-associated DCs was associated with the up-regulation of MALAT1, which subsequently increased the expression of Snail to promote tumor progression (42). A recent study also reported that IL-8 secreted from M2 macrophages sufficiently promoted the expression level of MALAT1 by activating the STAT3 signaling pathway (78). These studies suggest that MALAT1 serves as a key regulator during tumor progression, especially during tumor immune evasion.…”
Section: Expression Of Molecules In Tumor Cellsmentioning
confidence: 96%
“…Tumor microenvironment is very important for the growth, progression and metastasis of tumors, among which, inflammation is one of the most important factors [3][4]. Macrophage is one of the most common immune related cells in tumor microenvironment, and its functions to tumors have already been well documented in many cancers, such as pancreatic cancers [5][6], prostate cancers [7][8], lung cancers [9] and so on. Macrophages can be differentiated into classically (M1) and alternatively (M2) activated polar cells based on different environment situations.…”
Section: Introductionmentioning
confidence: 99%
“…MALAT1 is a lncRNA associated with the progression of various human cancers. 12,14,15 The upregulation of MALAT1 has been observed in PC cells relative to normal prostate epithelial cells or adjacent normal prostate tissues. 25,26 Moreover, the expression level of MALAT-1 is correlated with higher Gleason score, PSA and tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…12 It has also been found to be overexpressed and served as a potential therapeutic target in PC. [13][14][15] Pan et al reported that quercetin promoted the apoptosis of fibroblast-like synoviocytes in rheumatoid arthritis by upregulating lncRNA MALAT1. 16 However, the relationship between lncRNA MALAT1 and quercetin treatment in PC is still unknown.…”
Section: Introductionmentioning
confidence: 99%